Horizontal Financial Ratio Analysis to Estimate the Chronological Period of Financial Difficulties at PT Garuda Indonesia 2013-2021 - Teti Chandrayanti; Rizka Hadya (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2023)
PT Garuda Indonesia is one of the state-owned companies experiencing financial distress because of complex. Financial distress condition can be analyzed based on financial statements. This article aims to investigate the financial performance of the company by using horizontal analysis of financial ratio to estimate chronological period of financial difficulties at PT Garuda Indonesia in 2013-2021. Financial distress that is not managed properly will effect to bankrupt condition. This study uses financial ratio that are liquidity ratio, solvability ratio, and profitability ratio to evaluate the financial distress condition of PT Garuda Indonesia. Data was obtained from financial position statement and income statement. The results of research shown that In 2013 the company has experienced illiquid continuously until 2021. This is an early signal of financial difficulties occurring. In 2014, there was an insolvency until the end of the analysis year.  Losses occurred in 2014, but the next 2 years experienced gains. Continuous losses occurred from 2017 to 2021. Illiquid, insolvency, and losses aggravated the condition of financial difficulties so that PT Garuda is currently in a insolvency bankrupt condition. Professional and integrated financial management is needed so that problems can be resolved immediately.